Návrh betonové konstrukce jednolodní haly - Richtr, Jan (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Diplomová práce se zabývá návrhem jednolodní železobetonové montované haly s jeřábovou dráhou. Předmětem návrhu a posouzení jsou prvky nosného příčného rámu. Sedlový vazník společné se sloupy je posouzen na MSÚ a MSP. Další část návrhu se zabývá návrhem železobetonového opláštění z panelů. Panely jsou navrženy na MSÚ na mimořádné účinky zatížení. Diplomová práce se zabývá i možným dodatečným prědepnutím sloupů předpínací výztuží a možností osazení haly jeřábem s větší nosností

The master's thesis deals with the design of a single-nave reinforced concrete prefabricated hall with a crane runway. The focus of the design and assessment is on the elements of the main transverse frame. The saddle girder, along with the columns, is assessed for the ultimate limit state (ULS) and the serviceability limit state (SLS). Another part of the design addresses the proposal of the reinforced concrete cladding made of panels. The panels are designed for the ULS under exceptional loading conditions. The master's thesis also explores the possibility of additional column prestressing with post-tensioning reinforcement and the potential installation of a crane with higher load capacity in the hall.
Design of concrete structure of industrial hall
Keywords: montovaná hala; jeřábová dráha; prefabrikát; předpjatý beton; předpjatý vazník; dodatečné předpjaté konstrukce; monolitický kalich; základový pas; těžké opláštění; železobetonové panely; krátká konzola; železobetonový sloup; Prefabricated hall; crane runway; prefabricate; prestressed concrete; prestressed girder; additional prestressed structures; cast-in-place footing; foundation strip; heavy cladding; concrete panels; short cantilever; concrete column